2013
DOI: 10.1016/j.ramb.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine: cardiovascular risk factor in children and adolescents?

Abstract: The aim of this study was to identify publications in literature that investigated Homocysteine (He) as a risk factor for CVD among children and adolescents. An active search for information in LILACS, IBECS, Science Direct, Medline and Cochrane Library databases was conducted using the following combination of keywords "homocysteine", "cardiovascular diseases", "child" and "adolescent". Fifteen articles were analyzed showing direct relationship with increasing age (8 studies) and male gender (10 studies), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…However, with regards to Hcy and cardiovascular disease in children and adolescents, some interesting conclusions emerged from the systematic review of Leal et al [101], conducted on studies published between 1997 and 2011 on this topic. The authors underlined these fundamental conclusions: (a) HHcy is positively correlated with MTHFR 677T and heterozygous MTHFR 677T/1298C, with cardiovascular disease, and with low levels of folate and B12; (b) Hcy levels increase with age, being higher in adolescents than in children, and are higher in males than in females; (c) a possible association exisits between high Hcy levels in children and adolescents and a positive parental history for cardiovascular diseases; (d) there is a positive correlation between high Hcy and overweight and obesity in children and adolescents, with an increased risk for cardiovascular diseases (CVD).…”
Section: Hhcy and Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with regards to Hcy and cardiovascular disease in children and adolescents, some interesting conclusions emerged from the systematic review of Leal et al [101], conducted on studies published between 1997 and 2011 on this topic. The authors underlined these fundamental conclusions: (a) HHcy is positively correlated with MTHFR 677T and heterozygous MTHFR 677T/1298C, with cardiovascular disease, and with low levels of folate and B12; (b) Hcy levels increase with age, being higher in adolescents than in children, and are higher in males than in females; (c) a possible association exisits between high Hcy levels in children and adolescents and a positive parental history for cardiovascular diseases; (d) there is a positive correlation between high Hcy and overweight and obesity in children and adolescents, with an increased risk for cardiovascular diseases (CVD).…”
Section: Hhcy and Cardiovascular Diseasesmentioning
confidence: 99%
“…The correlation between HHcy levels and increased risk of CVD in children and adolescents is not yet well clarified. In their review, Leal et al [101] found many studies concluding a positive parental history of CVD and HHcy in children and adolescents and studies showing HHcy levels in overweight or obese subjects [102]. The authors [101] suggested the need to investigate HHcy in conjunction with other parameters such as insulin levels (which have an inverse relationship with Hcy) and renal function to clarify the pathophysiological mechanism by which HHcy can increase the risk of CVD.…”
Section: Hhcy and Cardiovascular Diseasesmentioning
confidence: 99%
“…Homocysteine is a modifiable factor [ 14 ] and it is controlled by folate level [ 29 ]. However, folate is involved in homocysteine metabolism and the potential role in lowering homocysteine is still much debated.…”
Section: Discussionmentioning
confidence: 99%
“…Folate level is a well known modifying factor that affects circulating homocysteine level [ 6 ]. However, the association between adiposity and homocysteine in children is debated [ 12 13 14 ]. Therefore the present study was undertaken to prospectively study the impact of adiposity including characteristics at birth and postnatal growth on homocysteine levels in children at three years of age in an ongoing birth cohort in South Korea.…”
Section: Introductionmentioning
confidence: 99%
“…HCYS accumulation in the plasma can be correlated with cardiovascular disease 36,37 caused by endothelial dysfunc- tion, low density lipoprotein oxidation and monocyte adhesion. 33 All these physiological and biochemical dysfunctions cause peripheral artery disease, 38 myocardial infarction and coronary atherosclerotic disease.…”
Section: H-hcys and Cardiovascular Diseasesmentioning
confidence: 99%